2018
DOI: 10.1021/acs.nanolett.8b02689
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo RNA Inhibition by CD9-HuR Functionalized Exosomes Encapsulated with miRNA or CRISPR/dCas9

Abstract: In vitro and in vivo delivery of RNAs of interest holds promise for gene therapy. Recently, exosomes are considered as a kind of rational vehicle for RNA delivery, especially miRNA and/or siRNA, while the loading efficiency is limited. In this study, we engineered the exosomes for RNA loading by constructing a fusion protein in which the exosomal membrane protein CD9 was fused with RNA binding protein, while the RNA of interest either natively harbors or is engineered to have the elements for the binding. By p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
189
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(190 citation statements)
references
References 34 publications
1
189
0
Order By: Relevance
“…Other loading methods include engineered parental cell and microfluidic synthesis of biomimetic lipid nanoparticles. For example, Li et al (2019d) reported an engineered EV for RNA delivery by constructing a fusion protein CD9-HUR which has ultra-high affinity for miRNA, achieving enhanced RNA loading efficiency in EVs. Biomimetic lipid nanoparticles are therapeutic platforms with intrinsic biological characteristics and good delivery capacity that can partially mimic the cell surface profiles of RBCs, white blood cells, platelets, and even cancer cells.…”
Section: Limited Drug Loading Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Other loading methods include engineered parental cell and microfluidic synthesis of biomimetic lipid nanoparticles. For example, Li et al (2019d) reported an engineered EV for RNA delivery by constructing a fusion protein CD9-HUR which has ultra-high affinity for miRNA, achieving enhanced RNA loading efficiency in EVs. Biomimetic lipid nanoparticles are therapeutic platforms with intrinsic biological characteristics and good delivery capacity that can partially mimic the cell surface profiles of RBCs, white blood cells, platelets, and even cancer cells.…”
Section: Limited Drug Loading Efficiencymentioning
confidence: 99%
“…Sonication PTX (Cheng et al, 2017), catalase (Li et al, 2019c), small RNAs (Sun et al, 2010) High loading efficiency but not efficient for hydrophobic drugs High loading efficiency Extrusion Porphyrins , catalase (Li et al, 2019c) High drug loading efficiency but potential deformation of membrane High loading efficiency Freeze/thaw cycle Catalase (Li et al, 2019c), prepare hybrid exosomes (Li et al, 2019d) Exosomes may aggregate and the drugs loading efficiency is low Low loading efficiency…”
Section: Medium Loading Efficiencymentioning
confidence: 99%
“…Gene engineering method is applied to HEK-293T cell line to functionalize the CD9 tetraspanin with the RNA-binding protein HuR and then, they are modified with miR-155 or the clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 system. The produced EVs are effectively enriched by the above mentioned RNAs and in future these nanoconstructs need to be evaluated in some diseases such as liver cancer [186]. Table 5.…”
Section: Evs Type Nanotechnological Modification Application Referencementioning
confidence: 99%
“…Targeting and therapy of liver cancer [186] Exosomes from HEK 293T Functionalization: Lamp2b, fused to a fragment of IL-3 Load: Imatinib or BCR-ABL siRNA Inhibition of chronic myeloid leukemia growth [84] Exosomes from HEK 293T Functionalization: GE 11 peptide Load: let-7a miRNA…”
Section: Evs Type Nanotechnological Modification Application Referencementioning
confidence: 99%
“…Pi et al 104 presented another modified exosome that relied on RNA nanotechnology, which allowed cholesterol to anchor RNA and resulted in RNA liganddisplaying on membranal exosomes, when these exosomes integrated with prostate-specific membrane antigen aptamer or breast-specific EGFR aptamer, subsequently suppressed prostate and breast cancer xenograft. In order to better encapsulate miRNA in plasma-derived exosomes and preserves their target specificity, Li et al 105 designed an exosomes fused with CD9 and HuR that triggered the enrichment of miR-155 in EVs, subsequently was delivered to recipient cells and achieved the endogenous target specificity. Hobor et al 106 demonstrated an RNA-binding Syncrip's amino-terminal domain selectively targeted miRNA in exosome-like vesicles through the recognition between the N-terminal unit for RNA (NURR) and Syncrip's RRM 5 0 as well as hEXO sequence.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%